(untitled) (BIRDEM Medical Journal, 2023)
We report a case of 66-year-old female, who presented with features of hypercalcemia and developed acute kidney injury (AKI). Parathyroid hormone level was raised up to 740 pg/ml. Ultrasound and sestamibi scan suggested presence of a right sided parathyroid adenoma. A decision of right sided parathyroidectomy was taken. The sample that was sent for frozen section showed only thyroid tissue. No macroscopically visible or palpable nodule suspected to be parathyroid adenoma could be found. So, a decision of right hemithyroidectomy was taken and done accordingly. On routine histopathology a solid gray white nodule was found within thyroid tissue and it was confirmed microscopically as parathyroid adenoma. BIRDEM Med J 2023; 13(2): 116-118